Determination of Organ Doses in Radioiodine Therapy using Monte Carlo Simulation - Daryoush Shahbazi-Gahrouei; Saba Ayat (World Journal of Nuclear Medicine)
Radioactive iodine treatment is a type of internal radiotherapy that has been used effectively for the treatment of differentiated thyroid cancer after thyroidectomy. The limit of this method is its affects on critical organs, and hence dosimetry is necessary to consider the risk of this treatment. Scope of this work is the measurement of absorbed doses of critical organs by Monte Carlo simulation and comparing the results with other methods of dosimetry such as direct dosimetry and Medical Internal Radiation Dose (MIRD) method. To calculate absorbed doses of vital organs (thyroid, sternum and cervical vertebrae) via Monte Carlo, a mathematical phantom was used. Since iodine 131 ( 131 I) emmits photon and beta particle, FNx01F8 tallies, which give results in MeV were applied and the results were later converted to cGy by dividing by the mass within the cell and multiplying by 1.6E-8. The absorbed dose obtained by Monte Carlo simulations for 100, 150 and 175 mCi administered 131 I was found to be 388.0, 427.9 and 444.8 cGy for thyroid, 208.7, 230.1 and 239.3 cGy for sternum and 272.1, 299.9 and 312.1 cGy for cervical vertebrae. The results of Monte Carlo simulation method had no significant difference with the results obtained via direct dosimetry using thermoluminescent dosimeter-100 and MIRD method. Hence, Monte Carlo is a suitable method for dosimetry in radioiodine therapy.